2016
DOI: 10.1103/physreva.94.012302
|View full text |Cite
|
Sign up to set email alerts
|

Multiqubit entanglement in bidirectional-chiral-waveguide QED

Abstract: We study the generation of entanglement induced by a single-photon Gaussian wavepacket in multi-atom bi-directional waveguide QED. In particular, we investigate the effect of increasing the number of atoms on the average pairwise entanglement. We demonstrate by selecting smaller decay rates and in chiral waveguide settings, that both entanglement survival times and maximum generated entanglement can be increased by at least a factor of ∼ 3/2, independent of the number of atoms. In addition, we analyze the infl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(63 citation statements)
references
References 58 publications
0
63
0
Order By: Relevance
“…Of particular interest in 1D waveguide systems is the identification of excitation probabilities of quantum systems and photon scattering amplitudes. These have been computed using various methods [21][22][23][24][25][26][27][28][29], but often semi-analytically (that is, through a combination of analytical and numerical methods). While semi-analytical approaches are quite reliable for calculating excitation probabilities of atoms and single-photon scattered pulse shapes [26,30,31], a fully analytical treatment of quantum networks would deepen intuition and enhance understanding by making clear the general relationship between the system's parameters and its behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in 1D waveguide systems is the identification of excitation probabilities of quantum systems and photon scattering amplitudes. These have been computed using various methods [21][22][23][24][25][26][27][28][29], but often semi-analytically (that is, through a combination of analytical and numerical methods). While semi-analytical approaches are quite reliable for calculating excitation probabilities of atoms and single-photon scattered pulse shapes [26,30,31], a fully analytical treatment of quantum networks would deepen intuition and enhance understanding by making clear the general relationship between the system's parameters and its behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Is such dynamics NM?The key task is to find the dynamical map (DM) of the qubit in the scattering process, which fully describes the open dynamics and is needed in order to apply OQS tools [38]. A distinctive feature of our open dynamics is that the bath (the waveguide field) is initially in a well-defined single-photon state [43,44]. Toward this task, we tackle in full the time evolution of multiple excitations (in contrast to those limited to the one-excitation sector [43,[45][46][47][48]), a problem that has become important recently [30,31,33,[49][50][51][52][53][54][55][56][57].Intuitively, one may expect that the dynamics is fully Markovian in the infinite-waveguide case and NM in the semi-infinite case due to the atom-mirror delay time.…”
mentioning
confidence: 99%
“…On the other hand, the creation of quantum entanglement has always been a fundamental task for quantum computation and quantum information processing [19]. In recent years, there has been much attention paid on establishing quantum entanglement in regular [20][21][22][23][24][25][26] and chiral [27][28][29][30][31][32][33] waveguide QED systems. In particular, it is shown that, by mere coupling to an infinite waveguide, qubits could establish effective interaction and twoqubit entanglement can be generated spontaneously [20-24, 28, 29].…”
Section: Introductionmentioning
confidence: 99%